A Novel Certification Process for Component-Based Life Cycle Model - Chopra, Sandeep; Sharma, M.K; Nautiyal, Lata (International Journal of Computer Sciences and Engineering, 2025)
Reusing the module or component of software is one of the most prime objective while developing a software system. To design computer program from the bottom or scratch is extremely expensive and time consuming so most of the giant companies in the field of computers are using pre- existing software components. CBSE i.e component based software engineering depends on the concept of combining different- components, providing interfaces and integrating all the modules or components. The concept of certification helps us to believe that a component is up to the mark and it follows a particular quality standard which is the reliability of a particular component. Through this novel certification model we are introducing a new mechanism that helps to select the component from the repository which increases the reliability of a component